Influence of spermidine priming on rice (Oryza sativa) seed germinability and vigour under heat stress - H R ARCHANA; DUNNA VIJAY; MANJUNATH PRASAD C T; DILSHAD AHMAD; ARUN KUMAR M B; PROLAY KUMAR BHOWMICK; SUBODH KUMAR SINHA; D K SHARMA; L C SUSHMITHA (The Indian Journal of Agricultural Sciences, 2023)
Polyamines (PAs) play a vital role in plants' response to various abiotic stresses, including high temperature (HT) stress. The present study was carried out during 2020–23 at the Indian Agricultural Research Institute, New Delhi to explores how spermidine treatment affects rice (Oryza sativa L.) seeds' ability to withstand heat and the availability of sugars for seedling growth during the radicle stage in heat-susceptible (IR64) and tolerant (N22) varieties. The seeds were primed with 1 mM spermidine using PEG (-1 MPa) as the priming medium, followed by exposure to heat stress. Results showed that in unprimed seeds, heat stress significantly reduces the seed germination, vigour and sugar availability in both the varieties and to a greater extent in IR64 compared to N22. This difference resulted in a substantially lower percentage of normal seedlings and seed vigour index in IR64 than in N22. However, spermidine seed priming enhanced thermotolerance in both varieties, more in IR64, equating the normal seedling percentage and seedling growth with control, i.e. without heat stress. The priming treatment also notably augmented α-amylase activity and reducing sugar availability, particularly in N22, enabling better seedling growth under heat stress conditions. This study underscores the importance of seed priming with spermidine to allow the seedlings to tolerate elevated temperatures and maintain better seedling growth due to the enhanced availability of reducing sugars during germination and early seedling growth.